Legalpreneur's Legal Responsibilities Towards Clients in Online Legal Consultation Service Agreements - Indana Zulfah; Gurda Bram Raja Iskandar Muda Siregar; Anwar Fuad Alamsyah Lubis (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
The development of information technology has led to the emergence of online legal consultation services provided by legalpreneurs as business actors in the legal services sector. This phenomenon raises legal implications, particularly regarding the liability of legalpreneurs toward clients in online legal consultation service agreements. This study aims to analyze the legal relationship between legalpreneurs and clients, as well as to examine the legal responsibilities arising in cases of breach of contract or losses incurred during the provision of services. The research employs a normative juridical method with statutory and conceptual approaches. The results indicate that the relationship between legalpreneurs and clients is based on a legally valid electronic agreement, which creates rights and obligations for both parties. Legalpreneurs are civilly liable for any losses suffered by clients due to negligence, errors, or non-compliance with the agreed services. In addition, such liability also encompasses aspects of personal data protection and the confidentiality of client information. Therefore, clearer regulations and professional ethical standards are required to ensure legal certainty and protection for all parties involved in online legal consultation services.